Vật liệu mao quản trung bình Cu/SBA-15 được tổng hợp bằng phương pháp trao đổi ion - Đức và cộng sự, Hoàng Văn (Vietnam Journal of Chemistry, 2014)
Cu-containing SBA-15 mesoporous (Cu/SBA-15) material has been prepared based on silica SBA-15 solid exchanged with Cu(II)-ion solution under appropriate condition. The obtained samples were characterized by atomic absorption spectrometry (AAS), powder X-ray diffraction (XRD) and nitrogen adsorption/desorption measurement. The investigated results show that the prepared samples have highly ordered hexagonal mesostructure with large specific surface area and uniform mesopore size distribution. Catalytic performance of the Cu/SBA-15 material is investigated through the oxidation of red phenol by hydrogen peroxide as oxidizing agent. The Cu/SBA-15 catalyst exhibited an excellent catalytic activity.